Ordinance No. 377, §§ 2-4, Wenatchee City Council (1911) (Wenatchee, Washington). - (:unkn) unknown (My University, 1911)
It shall be unlawful for any person to carry upon his person any concealed weapon, consisting of either a revolver, pistol or other firearm or any knife (other than an ordinary pock§et knife) or any dirk or dagger, sling shot or metal knuckle or any instrument by the use of which injury could be inflicted upon the person or property of another person, provided, that this section shall not ap§ply to police officers and other persons whose duty it is to execute process or warrants or to make arrests.It shall be unlawful for any person to draw any species of firearm or any dirk, dagger, knife or other dangerous or deadly weapon in the presence of another with intent to intimidate, an§noy or injure another person. FIRING ARMS OR EXPLOSIVES. It shall be unlawful for any person to fire or discharge any cannon, gun, pistol, revolver, or any firearm of any description, or fire, or explode, or set off any squib, cire cracker, torpedo or other thing containing powder or other explosive material, except on days of public celebration or jubilee, and then only in the manner provided by the Ordinances of the City of Wenatchee."
Keywords: BRANDISHING; CARRY - CONCEALED; DISCHARGE